The performance effect of centralizing a nation`s elite swim program - Allen, S. V.; Vandenbogaerde, T. J.; Hopkins, W. G. (International Journal of Sports Physiology and Performance, 2015)
Many national sporting organizations recruit talented athletes to well-resourced centralized training squads to improve their performance. Purpose: To develop a method to monitor performance progression of swimming squads and to use this method to assess the progression of New Zealand`s centralized elite swimming squad. Methods: Best annual long-course competition times of all New Zealand swimmers with at least 3 y of performances in an event between 2002 and 2013 were downloaded from takeyourmarks.com (~281,000 times from ~8500 swimmers). A mixed linear model accounting for event, age, club, year, and elite-squad membership produced estimates of mean annual performance for 175 swim clubs and mean estimates of the deviation of swimmers` performances from their individual quadratic trajectories after they joined the elite squad. Effects were evaluated using magnitude-based inferences, with a smallest important improvement in swim time of -0.24%. Results: Before 2009, effects of elite-squad membership were mostly unclear and trivial to small in magnitude. Thereafter, both sexes showed clear additional performance enhancements, increasing from large in 2009 (males -1.4% ± 0.8%, females -1.5% ± 0.8%; mean ± 90% confidence limits) to extremely large in 2013 (males -6.8% ± 1.7%, females -9.8% ± 2.9%). Some clubs also showed clear performance trends during the 11-y period. Conclusions: Our method of quantifying deviations from individual trends in competition performance with a mixed model showed that Swimming New Zealand`s centralization strategy took several years to produce substantial performance effects. The method may also be useful for evaluating performance-enhancement strategies introduced at national or club level in other sports.